Kajian Penerapan Arsitektur Biomimikri (Studi Kasus Bangunan Eastgate Centre) - Abda Ibril, Zakky Fuad; Safeyah, Muchlisiniyati (Universitas Medan Area, 2025)
This research aims to examine the application of biomimicry architecture through a case study of the Eastgate Center building. Biomimicry architecture explores natural principles to design efficient and sustainable solutions in the built environment. A case study of the Eastgate Centre, a commercial building located in Harare, Zimbabwe, provides an opportunity to evaluate how biomimicry principles were applied in the design and construction of the building. The research method involved an in-depth literature review of the concept of biomimicry, structural and functional analysis of the Eastgate Center building, as well as interviews with architects and related parties. The results of this research provide insight into the effectiveness of applying biomimicry architecture in the context of commercial buildings and its contribution to energy efficiency, temperature regulation and environmental sustainability. These findings are expected to contribute to further understanding of the potential of biomimicry architecture in supporting the construction of more environmentally friendly and efficient buildings.